TRANSFORMATION OF QUANTITY INTO CONCEPT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article will show the specifics of the concept of “quantity” as well as the linguistic features. The article reflects the manifestation of the same features in the cross section of different languages.